Fuzzy Entropy in Adaptive Fuzzy Weighted Linear Regression Analysis with Application to Estimate Infant Mortality Rate - Abbas , Ahmad Farouk; Mohammed , Mohammed Jassim (Iraqi Journal of Science, 2022)
An adaptive fuzzy weighted linear regression model in which the output is basedon the position and entropy of quadruple fuzzy numbers had dealt with. The solutionof the adaptive models is established in terms of the iterative fuzzy least squares byintroducing a new suitable metric which takes into account the types of the influenceof different imprecisions. Furthermore, the applicability of the model is made byattempting to estimate the fuzzy infant mortality rate in Iraq using a selective set ofinputs.